KUALITAS VIRGIN COCONUT OIL DARI BEBERAPA METODE PEMBUATAN - Pontoh, Julius; Surbakti, Mariana Br.; Papilaya, Mayz (Sam Ratulangi University, 2008)
A research had been conducted to study the quality of Virgin Coconut Oils (VCOs) by various processing methods including step-wise heating, oil addition, and fermentation. Various parameters were measured to study the quality of VCOs from three processing methods including oil content, water content, free fatty acids content and peroxide value. The collected data was analyzed statistically following the analysis of variance (ANOVA) followed by the Least Significant Difference (LSD)Test. The results showed that the highest oil content was found from the VCO processed by oil addition method but did not significantly different with that processed by step-wise heating and fermentation methods. The highest water content was found from VCO processed by step wise heating, but not significantly different with that processed by fermentation. The lowest free fatty acid content was found from VCO processed by stepwise heating, and significantly different with that from VCO processed by fermentation, but not significantlÂ different with that from VCO processed by oil addition. The lowest peroxide value was found from VCO processed by fermentation, but not different to that from VCO processed by both stepwise heating and oil addition. Stepwise heating produced VCO with very hight quality followed by VCO processed by oil addition. Fermentation method produced VCO with very low quality.